Fazbear frights graphic novel collection, volume 5 ebook - Cawthon, Scott (Five Nights at Freddy's: Fazbear Frights Graphic Novel, 2024)
Don't miss this pulse-pounding collection of three novella-length comic stories that will keep even the bravest player up at night . . . Frustrated by an unfair arcade game, Colton throws himself into re-engineering the device at any cost . . . Mott quickly flushes his brother's creepy new pets down the drain, but the creatures have other plans . . . Aimee finally works up the courage to ditch her loud-mouthed, annoying friend at Freddy Fazbear's Pizza. But when it comes to Five Nights at Freddy's, even the most ordinary seeming actions can reap horrible consequences. In this volume, three stories from the New York Times bestselling Fazbear Frights series come to life in delightfully horrifying comics. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddy's fans.